Lost and found...Tracking a swallowed denture: Role of radiology - Yogita Khalekar; Amit Zope; Shobhit Saxena; Kunal Shah (Wolters Kluwer Medknow Publications, 2017)
Denture ingestion or aspiration is a problem requiring awareness of different specialists including dentists, surgeons, otolaryngologists, and anesthesiologists for prevention, early diagnosis and adequate treatment. Complications of swallowed dentures include hollow viscous necrosis, perforation, and penetration to neighbouring organs leading to fistulae, bleeding and obstruction. Here, we present the case of a 65 year old female patient who swallowed the denture, which was detected by barium swallow and removed by endoscopy. Hence, the management of swallowed denture needs a multidisciplinary approach with the help of a dentist, otolaryngologist and anesthesiologists. Dentists should recommend patients to visit them for planned check ups or revisit them in case of denture dislodgement or loosening as soon as possible to prevent such life threatening events.